Investigating the relationship between age of onset of depressive disorder and cognitive function. (27th September 2018) - Eraydin, Irem Ece; Mueller, Christoph; Corbett, Anne; Ballard, Clive; Brooker, Helen; Wesnes, Keith; Aarsland, Dag; Huntley, Jonathan
Abstract : Objectives: Depressive disorder is commonly associated with impaired cognitive function; however, it is unclear whether the age of onset of the first episode of depression, current depression severity, or historical severity of depressive episodes are associated with cognitive performance. Methods: This study examined baseline cross‐sectional data from the ongoing online PROTECT study. A total of 7344 participants, 50 years or older, with a history of depression and no diagnosis of dementia were divided into three groups according to age of onset of their first depressive episode: early‐onset, midlife‐onset, and late‐onset. Performance on measures of visuospatial episodic memory, executive function, verbal working, and visual working memory were evaluated. Demographic and clinical characteristics such as age, education, and severity of symptoms during their worst previous depressive episode and current depression severity were included in multivariate regression models. Results: The late‐onset depression group scored significantly lower on the verbal reasoning task than the early‐onset group while there were no significant differences found on the other tasks. Midlife‐onset depression participants performed better in the visual episodic memory task, but worse on the verbal reasoning task, than early‐onset depression participants. Current depression severity was negatively correlated with all four cognitive domains, while historical severity score was found to be significantly associated with cognitive performance on the verbal reasoning and spatial working memory tasks. Conclusions: The most important indicator of cognitive performance in depression appears to be current, rather than historic depression severity; however, late‐onset depression may be associated with more executive impairment than an early‐onset depression.